A 32-bit carry lookahead adder using dual-path all-N logic. - Ge Yang
We have developed dual path all-N logic (DPANL) and applied it to 32-bit adder design for higher performance. The speed is significantly enhanced due to reduced capacitance at each evaluation node of dynamic circuits. The power saving is achieved due to reduced adder cell size and minimal race problem. Post-layout simulation results show that this adder can operate at frequencies up to 1.85 GHz for 0.35-μm 1P4M CMOS technology and is 32.4% faster than the adder using all-N transistor (ANT). It also consumes 29.2% less power than the ANT adder. A 0.35-μm CMOS chip has been fabricated and tested to verify the functionality and performance of the DPANL adder on silicon.
Keywords: 0.35 micron; 32 bit; ANT; CMOS chip; CMOS technology; DPANL adder; All-N transistor; Dual-path all-N logic; Dynamic logic circuit; Lookahead adder; Low power design; Post-layout simulation